Analysis and selection of experimental models of osteoarthritis - Grygorieva, O. A.; Monina, O. V.; Skakovsky, E. R.; Григор'єва, Олена Анатоліївна; Моніна, О. В.; Скаковський, Едуард Романович; Григорьева, Е. А.; Монина, Е. В.; Скаковский, Э. Р. (ЗДМУ, 2014)
Aim. The aim of the work is to examine relevant literature on different patterns of experimental osteoarthritis and choose the most acceptable one for providing its preclinical investigation. Methods and results. Osteoarthritis (OA) is one of the common forms of joint disease. OA is mainly in the head of the top fi ve causes of disability. Notwithstanding a great number of revealed predisposing factors and the involvement of mechanical distress, the exact pathogenesis of OA is still a subject of investigation. Particularly the earliest changes are largely unknown, because they appear long before clinical manifestation, and that is why they are not able to be studied in humans. The great number of OA researches is devoted to the methods of early detection and developing strategies of its treatment. Animal experimental models help in investigating mechanisms of OA development and fi nding morphological, physiological criteria for strict diagnosis of OA. Conclusion. It was settled that small animal experimental models of OA are more suitable for preclinical investigations of OA pathogenesis: its genetic and molecular mechanisms; large animal experimental models of OA allow to investigate biomechanical changes of the joint and to provide intraarticular interventions. Methods which are necessary for perfect investigation of the joint are also described in the article. Особливу увагу приділяють нині виявленню та вивченню ранніх змін у структурах суглоба (суглобовому хрящі, суглобовій капсулі, субхондральній кістці), які з’являються до маніфестування клінічних симптомів, що не можливо вивчити на людині. Мета роботи полягала в аналізі відомостей сучасної фахової літератури щодо окремих експериментальних моделей остеоартрозу на лабораторних тваринах й описі найбільш прийнятної моделі для виконання морфологічного дослідження. Встановили, що експериментальні моделі остеоартрозу з використанням невеликих лабораторних тварин (щури, мурчаки, миші, кролі) оптимальні для вивчення генетичних і молекулярних основ патогенезу остеоартрозу. Експериментальні моделі остеоартрозу з використанням великих лабораторних тварин (собаки, свині тощо) оптимальні для вивчення біомеханічних особливостей реактивності суглобів та виконання внутрішньосуглобових втручань. Особое внимание сегодня уделяют установлению и изучению ранних изменений в структурах сустава (суставном хряще, суставной капсуле, субхондральной кости), предшествующих появлению клинических симптомов, которые невозможно изучить у человека. Цель работы – проанализировать данные современной специализированной литературы о различных моделях экспериментального остеоартроза на лабораторных животных и выбрать наиболее приемлемую модель для морфологического исследования. Установлено, что экспериментальные модели остеоартроза с использованием мелких лабораторных животных (мыши, крысы, морские свинки, кролики) оптимальны для изучения генетических и молекулярных основ патогенеза остеоартроза. Экспериментальные модели остеоартроза с использованием крупных животных (собаки, лошади, овцы, свиньи) оптимальны для изучения биомеханических особенностей реактивности сустава, проведения внутрисуставных вмешательств.
Аналіз і вибір експериментальної моделі остеоартрозу
Анализ и выбор экспериментальной модели остеоартроза
Keywords: Osteoarthritis; Pathogenesis; Experimental animal model; Articular cartilage; Subchondral bone; остеоартроз; етіологія; експериментальна модель; суглобовий хрящ; этиология; экспериментальная модель; суставной хрящ